Manajemen Farmakologis Penyakit Hati Berlemak Non-Alkoholik (NAFLD) dalam Upaya Penurunan Prevalensi Penyakit Ginjal Kronis: Tinjauan Sistematis Perspektif Epidemiologi Terapan - Anak Agung Ngurah Oka Parama Wangsa; Ni Komang Ayu Diah Suryandari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Non-alcoholic fatty liver disease (NAFLD) is a global health problem frequently associated with diabetes mellitus and obesity. This condition increases the risk of renal dysfunction and liver fibrosis progression, highlighting the need for comprehensive therapeutic strategies. This study aimed to evaluate the medium-term effects of SGLT2 inhibitors on renal function and fibrosis progression in patients with NAFLD and metabolic diseases. This study employed a brief systematic review approach by analyzing relevant national and international scientific articles. Literature selection was conducted systematically based on predefined inclusion and exclusion criteria. The findings demonstrated that SGLT2 inhibitors were associated with improved or stabilized renal function, particularly in estimated glomerular filtration rate and albuminuria parameters. Moreover, most studies reported improvements in non-invasive fibrosis indicators and reductions in hepatic steatosis and inflammation. These benefits were closely related to better glycemic control and weight reduction in patients with metabolic comorbidities. In conclusion, SGLT2 inhibitors show potential as an adjuvant therapy in managing NAFLD patients with metabolic diseases by providing combined renal and hepatic protective effects.